Improving Students’ Writing Exposition Text By Using Four Square Writing Method Of The Eleventh Grade Science At Senior High School - Juanda; Ibrahim, Muliaty; Sujarwo, Sujarwo (CV. Eureka Murakabi Abadi, 2025)
The teaching of writing in Senior High Schools is still hampered by a number of problems. This study aims to describe implementation of classroom actions using the FSWM learning and describe the model on students 'exposition text writing skills exposition text the 11th grade students at SMA Negeri Negeri 12 Makassar. This classroom action research was conducted in one XI IPA4 class of SMA Negeri 12 Makassar with 36 students from March to May 2020. The study involved two cycles of planning, action, observation, and reflection, utilizing the Four Square Writing Method (FSWM) to improve students' exposition writing skills, with data collected through tests, questionnaires, observations, and field notes, and analyzed using qualitative and quantitative techniques. The research found that the Four Square Writing Method (FSWM) effectively improved both the process and product of writing exposition texts for XI IPA 4 students at SMA Negeri 12 Makassar. Process improvements included increased student engagement, active participation, positive responses to the learning model, and conducive classroom interactions, while product success was reflected in enhanced writing skills. This research concludes by demonstrating the effectiveness of the Four Square Writing Method (FSWM) in enhancing students' exposition text writing skills while fostering a more interactive and conducive learning process.